Corneal endothelial cell density and associated factors among adults at a regional referral hospital in Uganda: a cross-sectional study - Namwase, Shamiim; Ruvuma, Sam; Onyango, John; Kwaga, Teddy; Ebong, Abel; Atwine, Daniel; Mukunya, David; Arunga, Simon (BioMed Central Ltd, 2024)
Background To assess the prevalence of low corneal endothelial cell density and correlates of corneal endothelial cell density among adults attending Mbarara University and Referral Hospital Eye Centre in Uganda. Methods In this hospital-based cross-sectional study, participants 18 years and older, were enrolled. We obtained informed consent, and basic demographic data. We also conducted visual acuity, a detailed slit lamp examination, intra-ocular pressure, corneal diameter, tear-film break-up time, keratometry, A-scan, and pachymetry on all participants. A confocal microscope Heidelberg HRT3 was used to examine the central cornea and to obtain the mean cell density (cells/mm.sup.2). To calculate the proportion of low endothelial cell density, descriptive statistics were used, whereas correlates of endothelial cell density were assessed, using linear regression analyses. Results We evaluated a total of 798 eyes of 404 participants aged between 18 and 90 years (males = 187, females = 217). The average endothelial cell density was 2763.6 cells/mm.sup.2, and there was a decrease in endothelial cell density with increasing age, irrespective of gender. There was no significant difference in endothelial cell density between males and females. Increasing age (adjusted coefficient - 10.1, p < 0.001), history of smoking (adjusted coefficient - 439.6, p = 0.004), history of ocular surgery (adjusted coefficient - 168.0, p = 0.023), having dry eye (adjusted coefficient - 136.0, p = 0.051), and having arcus senilis (adjusted coefficient - 132.0, p = 0.08), were correlated with lower endothelial cell density. However, increasing corneal diameter (adjusted coefficient 134.0, p = 0.006), increasing central corneal thickness (adjusted coefficient 1.2, p = 0.058), and increasing axial length (adjusted coefficient 65.8, p = 0.026), were correlated with higher endothelial cell density. We found five eyes (0.63%) from different participants with a low endothelial cell density (< 1000cells/mm.sup.2). Conclusion Our study established baseline normal ranges of ECD in a predominantly black African population, and found that low ECD is rare in our population. The elderly, smokers, and those with past ocular surgery are the most vulnerable. The low prevalence could be due to a lack of reference values for the black African population. Keywords: Cornea, Endothelial cell density, Uganda
Keywords: Cornea, Endothelial cell density, Uganda